CysLT(1) leukotriene receptor antagonists inhibit the effects of nucleotides acting at P2Y receptors - Mamedova, Liaman (Biochem Pharmacol, 2005)
Montelukast and pranlukast are orally active leukotriene receptor antagonists selective for the CysLT(1) receptor. Conversely, the hP2Y(1,2,4,6,11,12,13,14) receptors represent a large family of GPCRs responding to either adenine or uracil nucleotides, or to sugar-nucleotides. Montelukast and pranlukast were found to inhibit nucleotide-induced calcium mobilization in a human monocyte-macrophage like cell line, DMSO-differentiated U937 (dU937). Montelukast and pranlukast inhibited the effects of UTP with IC(50) values of 7.7 and 4.3 μM, respectively, and inhibited the effects of UDP with IC(50) values of 4.5 and 1.6 μM, respectively, in an insurmountable manner. Furthermore, ligand binding studies using [(3)H]LTD(4) excluded the possibility of orthosteric nucleotide binding to the CysLT(1) receptor. dU937 cells were shown to express P2Y(2), P2Y(4), P2Y(6), P2Y(11), P2Y(13) and P2Y(14) receptors. Therefore, these antagonists were studied functionally in a heterologous expression system for the human P2Y receptors. In 1321N1 astrocytoma cells stably expressing human P2Y(1,2,4,6) receptors, CysLT(1) antagonists inhibited both the P2Y agonist-induced activation of phospholipase C and intracellular Ca(2+) mobilization. IC(50) values at P2Y(1) and P2Y(6) receptors were <1 μM. In control astrocytoma cells expressing an endogenous M3 muscarinic receptor, 10 μM montelukast had no effect on the carbachol-induced rise in intracellular Ca(2+). These data demonstrated that CysLT(1) receptor antagonists interact functionally with signaling pathways of P2Y receptors, and this should foster the study of possible implications for the clinical use of these compounds in asthma or in other inflammatory conditions.